2019
DOI: 10.1073/pnas.1900238116
|View full text |Cite
|
Sign up to set email alerts
|

Reverse engineering field-derived vertical distribution profiles to infer larval swimming behaviors

Abstract: Biophysical models are well-used tools for predicting the dispersal of marine larvae. Larval behavior has been shown to influence dispersal, but how to incorporate behavior effectively within dispersal models remains a challenge. Mechanisms of behavior are often derived from laboratory-based studies and therefore, may not reflect behavior in situ. Here, using state-of-the-art models, we explore the movements that larvae must undertake to achieve the vertical distribution patterns observed in nature. Results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…In the present study, M. gigas was assumed to exhibit upward migration during the rising tide and downward migration during the falling tide in line with observations for other bivalve species (Newell et al 2005). A recent study (James et al 2019) used observed vertical distributions of another bivalve species (Mytilus spp.) to infer the vertical swimming behaviour and concluded that an asymmetrical tidally driven migration where larvae swim up at the start of flood but start swimming downward at mid-flood was most appropriate.…”
Section: Modelling Considerationssupporting
confidence: 65%
See 1 more Smart Citation
“…In the present study, M. gigas was assumed to exhibit upward migration during the rising tide and downward migration during the falling tide in line with observations for other bivalve species (Newell et al 2005). A recent study (James et al 2019) used observed vertical distributions of another bivalve species (Mytilus spp.) to infer the vertical swimming behaviour and concluded that an asymmetrical tidally driven migration where larvae swim up at the start of flood but start swimming downward at mid-flood was most appropriate.…”
Section: Modelling Considerationssupporting
confidence: 65%
“…This is on the upper limit (0.001-0.003 ms -1 ) of estimates for Mytilus spp. (James et al 2019). During Stage 3, the larvae were competent to settle and swim towards the bed (Arakawa 1990).…”
Section: Spawning and Larval Developmentmentioning
confidence: 99%
“…Given that dispersal is a key process shaping the distribution of marine species by mediating connectivity and recruitment within and among patches (James et al., 2019), the presence and duration of fronts could affect the dispersal and population dynamics of a species, thereby affecting long‐term trends in abundance and distribution (Ayata et al., 2010; Pringle et al 2017). For instance, Banks et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest complex decision‐making processes undertaken by barnacles and other early‐life history stages of marine taxa during settlement in response habitat features including surface roughness (Berntsson et al 2004, Herbert and Hawkins 2006), biochemical signals (Dreanno et al 2007), surface orientation and other biological cues (Harrington et al 2004, Hanlon et al 2018). Selection of ‘preferred' habitat at small spatial scales may therefore be less likely (James et al 2019), with larval retention and recruitment patterns instead, determined by physical processes associated flow characteristics created by surface rugosity (Lim et al 2020). Our results suggest a degree of selectivity for a specific basibiont is apparent between barnacle species that cannot be explained by this study, but might include surface environment chemistry (McManus et al 2018), surface rugosity of the basibiont shell and surrounding rock, or the diversity of the surrounding community providing chemical cues (Huggett et al 2005).…”
Section: Discussionmentioning
confidence: 99%